Household Behaviour, Prices, and Welfare A Collection of Essays Including Selected Empirical Studies - Ray, Ranjan (Themes in Economics, Theory, Empirics, and Policy,, 2018)
This collection of essays covers a diverse set of topics related to household behavior and welfare. Prices play a key role in several of the essays, particularly the distributional implications of price movements, and the effects of changes in relative prices on inequality and poverty. This book shows the shift in the literature on prices from being an exclusively macro topic featuring the study of inflation and cross-country comparisons to one that is firmly rooted in micro theory-based analysis of household behavior. It also includes recent developments in the poverty measurement literature, documenting the shift from the exclusively money metric and unidimensional poverty measures to multidimensional poverty encompassing a wider view of deprivation. Largely, but not exclusively, focusing on India, the book also features global comparisons of welfare. Intra country spatial comparisons along with cross country comparisons of household behavior and welfare feature in several of the essays in this book. The book also compares the effects of selected public delivery schemes in India on the health of its children. It is a useful resource for researchers and serves as reading material for advanced graduate courses on development in India and elsewhere.